Comparison between Invasive & Non-Invasive Diagnostic Evaluation of Tuberculous Peritonitis In Our Prospective - Ali, Md Naushad; Parvin, Rehana; Azad, Md Abul Kalam; Islam, AKM Mazharul (Medicine Today, 2016)
This cross sectional study was carried out in the department of gastroenterology, Rangpur Medical College Hospital, Rangpur from January 2014 to July 2014 to compare between Invasive & Non-Invasive Diagnostic Evaluation of Tuberculosis Peritonitis In our prospective in clinically suspected patients. Total 30 patients (age 39.69±21.26, 18M/12F) with clinical suspicion of peritoneal tuberculosis were included in this study after analyzing selection criteria. Laparoscopic peritoneal biopsy with 'histopathological' diagnosis was considered as gold standard against which accuracies non-invasive test of two biomarkers (ADA & CA-125) were compared. Cut off value of ADA and CA-125 is 24 U/l, 35 U/ml respectively. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of ADA as a diagnostic modality in peritoneal tuberculosis were 87.5%, 83.33%, 95.45%, 62.5% and 86.67% respectively whereas CA-125 was found to have 83.33% sensitivity, 50% specificity, 86.9% positive predictive value, 42.85% negative predictive value and 76.6% accuracy. Both biomarkers were simple, non-invasive, rapid and relatively cheap diagnostic test whereas laparoscopy was an invasive procedure, costly & requires trained staff and not without risk and also not feasible in the entire centre in our country. So ascitic fluid ADA and serum CA-125 was important non-invasive diagnostic test for peritoneal tuberculosis. Medicine Today 2015 Vol.27(2): 20-22